USE OF EXPERT ASSESSMENT METHODS FOR DETERMINATION OF EFFICIENCY INDICATORS OF A TRADING ENTERPRISE: Array - Karpenko, M.; Shtelma, O.; Karas, P. (Municipal economy of cities. Series: «Economy science», 2022)
The article considers the use of expert methods to study the degree of influence of turnover on the efficiency of the trading company. A group of experts who took part in the relevant survey was involved in conducting the research. Technically, the survey was organized through a number of Google forms with further processing of results in the environment of MS Office 365. The following parameters were chosen for the research: profitability of maintenance, internal rate of return (IRR), response sensitivity (IRR), payback period, turnover ratio, minimization of inventories. The survey was conducted according to the Delphi method, ie it was iterative. Initially, the experts anonymously filled in the data on the feasibility of using certain indicators of turnover as a criterion for assessing the effectiveness of the trading company, using a single system of scoring. After statistical processing of the results and determination of the concordance coefficient, the results of the survey were provided to the expert group for review and, after which the next stage of the survey was conducted. This process was repeated until the level of consistency reached the desired level. As a result of the research, a decision was obtained with a coefficient of consistency of 0.964, according to which the three most important indicators were identified, namely: rating "VSD response sensitivity" (rating 1), "internal rate of return, %" (rating 2), profitability THAT,% ”(rating 3). The described approach was used in the design of a component of the existing information system, which is used in a number of trading companies and proved its effectiveness.